Karakteristik Daun Jarak Pagar (Jatropha curcas L.) dan Hubungannya dengan Fotosintesis - Ince Raden; Bambang S. Purwoko; , Hariyadi; Munif Ghulamahdi; Edi Santosa (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
The objective of this research was to study the morphology and physiology of jatropha leaves and its relation to photosynthesis. Research was conducted using Randomized Complete Block Design with single factor, i.e., leaf ages at the canopy with ten replications. The results showed that jatropha had phyllotaxy 5/13 with angular divergence 1380 . In early growing leaf enlarged sharply and then constant after 9 week, remaining green for 14 weeks. Chlorophyll a, b, and total achieved maximum at 9 week, i.e., 0.45 g/cm2 , 0.19 g/cm2 , and 0.62 g/cm2 , respectively. Photosynthesic rate was maximum at 6 week, i.e., 8.99 µmol/m2 /s, while number of stomata was maximum at 9 week (289.47 mm2 ). This finding implies that leaf number 11 to 13 or age 6 week after emergence could be used as reference for photosynthetic evaluation.